Ambiguitas dalam Humor Parikan/Pantun Kilat Sebagai Pelesetan Makna - M Hermintoyo (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
Language is a communication tool that can be done according to purpose, variety, and media. The goals expected in communicating can be for entertaining, joking and creativity. Creativity can be in the form of works of art, such as rhymes. Pantun in Javanese is called parikan. The constituent elements are bound by the rules of the pantuna form. Ordinary rhyme or four-row rhyme or flash rhyme consisting of two lines. But both must rhyme abab (cross rhyme); each row between four to twelve syllables; the first line is sampiran, the second line is the content (quick rhyme. If the regular rhyme of the first and second rows is sampiran; the fourth row is in the form of contents. The variety used in pantun is a variety of literature. The media can be oral, written, written). can be in print, and in electronic media through the internet. The contents of the pantun can be serious or not, for example the contents are only for humor. Based on the rhyme content data with multiple information / taxa / ambiguity. The tendency of the pantun content ambiguity in the data tends to be interpreted negative / connotative pornography .